Análise da acidentalidade viária em trechos urbanos da Rodovia Federal BR-369 no Estado do Paraná - Kondo, Bruno Hiroyuki (Universidade Federal de São Carlos, 2023)
Road accidents in Brazil may present a worsening in their occurrence in the post-pandemic scenario. It is expected that the conditions of the roads will deteriorate due to a decrease in public and private investments, as well as an increase in vehicle traffic, driven by the resumption of economic activities, leading to an increase in the occurrence of accidents. Thus, the present study aims to observe road accidents in urban sections of the federal highway BR-369 in the state of Paraná, between the years 2015 and 2021. Parameters such as accident occurrence, fatalities, accident rates, and road classification in terms of overall condition, pavement, geometry, and signage were analyzed according to the methodology developed by the National Confederation of Transport (CNT). To achieve this, data extraction and analysis were necessary using the information provided by the Federal Highway Police, the CNT Highway Survey, and the National Department of Infrastructure and Transport. Additionally, georeferencing software was used to visually identify critical sections. After data collection, processing, and calculation of indicators, sections that stood out due to the recurrence of accidents over the years were observed, especially in more urbanized regions with significant traffic volume. Through these results, it was possible to observe the influence of socioeconomic characteristics of the surrounding regions and road traffic on critical sections.
Analysis of road accidents in urban sections of Federal Highway BR-369 in the State of Paraná
Keywords: Acidentes de trânsito; BR-369; Segurança Viária; Infraestrutura viária; Trechos urbanos; ENGENHARIAS::ENGENHARIA DE TRANSPORTES::OPERACOES DE TRANSPORTES; ENGENHARIAS::ENGENHARIA DE TRANSPORTES::PLANEJAMENTO DE TRANSPORTES